The Olympics and philosophy - Reid, Heather Lynne, 1963-; Austin, Michael W. (Philosophy of popular culture., 2012)
It is said the champions of the ancient Olympic Games received a crown of olive leaves, symbolizing a divine blessing from Nike, the winged goddess of victory. While the mythology of the ancient games has come to exemplify the highest political, religious, community, and individual ideals of the time, the modern Olympic Games, by comparison, are widely known as an international, bi-annual sporting event where champions have the potential to earn not only glory for their country, but lucrative endorsement deals and the perks of worldwide fame. The Olympics and Philosophy examines the Olympic Movement from a variety of theoretical perspectives to uncover the connection between athleticism and philosophy for a deeper appreciation of the Olympic Pillars of Sport, Environment, and Culture. While today's Olympic champions are neither blessed by the gods nor rewarded with wreaths of olive, the original spirit and ancient ideals of the Olympic Movement endure in its modern embodiment. Editors Heather L. Reid and Michael W. Austin have assembled a team of international scholars to explore topics such as the concept of excellence, ethics, doping, gender, and race. Interweaving ancient and modern Olympic traditions, The Olympics and Philosophy considers the philosophical implications of the Games' intersection with historical events and modern controversy in a unique analysis of tradition and the future of the Olympiad.